BELONGING BEYOND POSSESSION: PSYCHOLOGICAL OWNERSHIP IN LOUISE ERDRICH’S LA ROSE - Sreelatha R. H.; Kumari, R. Janatha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Psychological Ownership is the feeling that the target object is one’s own. It extends beyond material possession to include people, places, culture and memory. Erdrich’s La Rose exhibits a complex narrative in which identity, restitution and the sense of belonging is comprehended through acts of extending, reclaiming and preserving. In La Rose, sense of self is asserted through the ownership and belongingness towards people and relationship. The paper, Belonging Beyond Ownership: Mapping Native Identity and Psychological Rootedness in Select Novels of Louise Erdrich, examines how the characters in the select novel, assert their identity and agency through the emotional belongingness with the people, family, ancestral ties, and cultural artefacts. Erdrich’s novel La Rose gives a clear picture of the journey of finding and asserting the real self from a shattered and dismantled identity. This paper explores how the sense of ownership makes people efficacious, responsible and more attached to the target object and finally assert their self-identity.